Satisfaction towards an enrichment programmes: Halal action for young scientists camp / Nur Fazidah Asmuje … [et al]. - Asmuje, Nur Fazidah; Zainal, Rosita; Abd Razak, Amnah Zanariah; Shafie, Ahmad Hakimi; Sabri, Nurul Elma; Jamil, Anis Liyana Nabihah (Research Management Centre (RMC), 2019)
Early teenager is a stage to develop individual interest, skills, and preferences which are salient for the future. An enrichment programme is one of the approaches to disclose teenager’s interest. This study aims to identify the effectiveness of Halal Action for Young Scientists Camp as an enrichment programme for secondary school students. A week-long camp were administered by Kolej PERMATA Insan USIM to expose ‘halal’ and ‘thoyyib’ education with scientific analysis. In addition, this study also identifies the elevation of science interest through five modules that were exposed through this camp. A survey was given to obtain the overall feedback of the camp including trainers, modules and facilities. Participants in this study were 22 students in total from various secondary schools in Malaysia who participated in the camp. The data analysis was calculated using descriptive and inferential statistic. The results of data processing shows that this camp was suitable as an enrichment programme through five related modules. Most of the students have deepened their interest in science after participating in this camp.